Koperasi Indonesia dalam Perekonomian yang Kompetitif dan Pasar Bebas - Indi Sutopo; Endang Sri Gunawati (EKO-REGIONAL, 2008)
The objective of this research is to study the philosophical fondation of Koperasi Indonesia. The important factor discussed in this research is cooperative philosophy concept. As the characteristic of Indonesian economy, Koperasi Indonesia should be convinced as the core economic system in Indonesia although the threat of the free competition outside is great enough.The research method used is literature study with empirical qualitative analysis. The researchers explore the advantage of Koperasi Indonesia and also the role of the government to encourage and strengthen the economic fondation because we can not escape from the great competition in the future. Koperasi Indonesia with the cooperative concept is the solution but it still needs the awareness and development of this concept as the economic system from whole parties in this country.        Keywords: cooperative, welfare, clasic economics, social economics